Pengaruh E-Wom Di Sosial Media Dan Kualitass Produk Terhadap Keputusan Pembelian Di Jeen Sneakers Blitar. - Sukma Ukhtina; N. Rachma; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract Global economic growth accompanied by technological advances encourages people's lifestyles. One of them is the pattern of shopping life which is now more practical, fast, and economical. The movement of modern industry that is mushrooming makes each industry to compete in order to maintain and improve the business that was founded.This study analyzes the effect of ewom on social media and product quality on purchasing decisions. The population in this study were 80 respondents. The sample in this study was 80 respondents using accidental sampling technique. Using primary, secondary and tertiary data and this research uses a questionnaire or questionnaire data collection method and interview data collection methods.The results of this study note that the results of the F test are known that the ewom variable on social media and product quality simultaneously have a significant effect on purchasing decisions. Keywords: Ewom on social media, product quality, purchasing decisions